Maintenance of liver fluke, Dicrocoelium dendriticum, outside the body of its native host - Mohsen Arbabi; Atefeh Hadad; Hossein Hooshyar; Hossein Akbari; Seyed Mostafa Hosseinpour Mashkani (International Archives of Health Sciences, 2021)
Aims: In vitro cultivation of digenea would help the development of effective treatments and studies of the biology of the parasites. The goal of the present study was to optimize culture conditions for the maintenance liver fluke, Dicrocoelium dendriticum. Materials and Methods: Forty fresh D. dendriticum were collected from the sheep liver and washed three times with warm Roswell Park Memorial Institute (RPMI) 1640 Medium. The collected worms were transferred to 24-well Nunc-Immuno plates containing RPMI media supplemented with 50% of fetal bovine serum (FBS), 2% of sheep red blood cells (RBCs), 50 IU/ml of penicillin, and 50 mg/ml streptomycin. The mobility of the live/dead worms was observed by inverted microscope. The mean and median survival time was calculated by Kaplan–Meier model, and survival and hazard function graphs were also analyzed. Results: D. dendriticum was lived in vitro only for long periods of about 25 dyes. The 1st day of maintaining in culture media, one worm was dead and the number of dead worms was raised to 40 after 25 days of incubation. On the one hand, the mean survival time was 392 h with a confidence interval (CI) of 95% (384.8–400.03). On the other hand, the median survival time was 420 h with a CI of 95% (406.9–433.09). D. dendriticum was able to be alive in RPMI 1640 media for at least 25 days. Conclusion: RPMI 1640 supplemented with FBS, and RBCs can be used as short-term maintenance for the in vitro culture of D. dendriticum. The outcomes of the current study could be useful for many aspects of parasitological analysis.